PRINCIPLES OF VOLODYMYR DERZHAVYN’S LITERARY SCIENTIFIC ANALYSIS - Басенко, Н. Б. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article give us an idea about the literary scientific methodology of diasporan researcher of literature Volodymyr Derzhavyn. The article reveals the basic principles of analysis of art compositions, methodological foundations of literary criticism, influence of formal and structural approaches on the scholar’s researches.